Power Relation: The existence of Petchaburi Shadow Puppetry - Somsriploy, Sombat; Imsamran, Bayan (Journal of the Faculty of Arts, Silpakorn University, 2020)
This article studies the power factors that contribute to the continuous existence of Petchaburi shadow play. The results show that these factors consist of 1) the power of the sacred world: while making a vow, the local sacred beings will take control of the host and puppeteers; 2) the power of the performing world: during the performance, the puppeteer will take control behind the screen. The audience would not realize the power because they were engrossed by the stories and the sense of humor created by the puppeteer; and 3) economic powers, namely individuals and temple representative committees who have the means to hire the performers and pay for the productions. The confluence of all three factors is generally harmonious and free of conflict. Consequently, they contribute to the maintenance the Petchaburi shadow play regardless of contemporary social change.